2018
DOI: 10.7150/jca.26120
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Albumin-to-Alkaline Phosphatase Ratio for Overall Survival of Hepatocellular Carcinoma Patients Treated with Trans-Catheter Arterial Chemoembolization Therapy

Abstract: Background: We have previously reported the prognostic value of the albumin-to-alkaline phosphatase ratio (AAPR) for advanced hepatocellular carcinoma (HCC) patients who are not receiving any standard anticancer therapy. However, the prognostic value of the AAPR for HCC patients treated with trans-catheter arterial chemoembolization therapy (TACE) was not investigated.Methods: We retrospectively analysed 372 HCC patients treated with TACE (the training cohort) and applied receiver operating characteristic curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
1
23
1
Order By: Relevance
“…This cutoff value, 0.39 for AAPR, was suggested as a superior prognostic level according to HR. Nevertheless, the cutoff-point was not consistent with those from previous studies [15][16][17]27] and was close to that of one study [14]. This common problem can also be observed in studies of other prognostic biomarkers, including the platelet-lymphocyte ratio and neutrophil-lymphocyte ratio [31].…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…This cutoff value, 0.39 for AAPR, was suggested as a superior prognostic level according to HR. Nevertheless, the cutoff-point was not consistent with those from previous studies [15][16][17]27] and was close to that of one study [14]. This common problem can also be observed in studies of other prognostic biomarkers, including the platelet-lymphocyte ratio and neutrophil-lymphocyte ratio [31].…”
Section: Discussioncontrasting
confidence: 51%
“…At the moment, some biomarkers from blood have been established, including the AST/ALT (De Ritis) ratio, the neutrophil-to-lymphocyte ratio, and the prognostic nutritional index [10][11][12], although their results remain inconsistent and controversial. Recently, the albumin-to-alkaline phosphate ratio (AAPR), a novel prognostic factor, has been demonstrated to be significantly associated with poorer urologic outcomes for hepatocellular carcinoma (HCC), metastatic nasopharyngeal carcinoma, and upper tract urothelial carcinoma (UTUC) [13][14][15][16][17]. However, it has not yet been studied in non-metastatic RCC patients following curative nephrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Since Chan et al 15 firstly reported the ratio of ALB to ALP combined with ALB and ALP levels can be used as an indicator for predicting the prognosis for patients with liver cancer, and such prediction ability is higher than that based on ALB or ALP levels alone, more studies began to investigate these indicators in other types of cancer. [7][8][9][10][16][17][18][19][20][21] Li et al 16 firstly reported that the relationship between AAPR and OS after investigating 290 stage IV NSCLC patients, finding that AAPR was an independent predictor of OS in multivariate analysis (HR = 0.657, 95% CI = 0.504-0.856, P < .01). Different from their study, we conducted a larger respective cohort as well as included more important variables for analysis, such EGFR and ALK mutation status, ECOG-performance status, therapeutic regiment, F I G U R E 4 Forest plot for presenting the association between the hazard ratio of overall survival and medium AAPR in advanced NSCLC patients and organ metastasis parameters, which have been verified to exert influence on the clinical outcome of the NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the current research, 15 retrospective articles with 6,062 cancer patients were included [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Because of the subgroup analysis in three articles [15,17,19], we regarded them as 2 or 3 independent studies. The publication dated from 2015 to 2019, and the number of cancer patients ranged from 82 to 746.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%